Apigenin: A natural bioactive flavone-type molecule with promising therapeutic function - Dharambir Kashyap; Ajay Sharma; Hardeep Singh Tuli; Katrin Sak; Vivek Kumar Garg; Harpal Singh Buttar; William N. Setzer; Gautam Sethi (Journal of Functional Foods, 2018)
There exist overwhelming evidence that plant-derived bioactive flavonoids possess strong therapeutic activities against cancer, cardiovascular diseases, and age-related neurodegenerative disorders. Several drug discovery studies have suggested the therapeutic potential of apigenin (APG) are due to its strong anti-inflammatory, anti-oxidant, and anti-tumor properties. APG is found in citrus fruits, vegetables, spices, and herbs. It is well documented that APG can modulate a wide variety of intra- and extra-cellular signaling pathways in in vitro cancer cell lines and in vivo neoplasm systems, and consequently retard or inhibit abnormal growth of tissues. Co-administration of APG with anti-cancer drugs has shown to increase the therapeutic potency of the later. The overall aims and objectives of this review are to highlight the potential role of APG in the prevention and treatment of different types of malignant human cancers. We will also describe different purported biochemical mechanisms associated with the inhibition of cancer cell proliferation and tumor growth.